3D bioprinting for skin tissue engineering: Current status and perspectives. (July 2021) - Weng, Tingting; Zhang, Wei; Xia, Yilan; Wu, Pan; Yang, Min; Jin, Ronghua; Xia, Sizhan; Wang, Jialiang; You, Chuangang; Han, Chunmao; Wang, Xingang
Skin and skin appendages are vulnerable to injury, requiring rapidly reliable regeneration methods. In recent years, 3D bioprinting has shown potential for wound repair and regeneration. 3D bioprinting can be customized for skin shape with cells and other materials distributed precisely, achieving rapid and reliable production of bionic skin substitutes, therefore, meeting clinical and industrial requirements. Additionally, it has excellent performance with high resolution, flexibility, reproducibility, and high throughput, showing great potential for the fabrication of tissue-engineered skin. This review introduces the common techniques of 3D bioprinting and their application in skin tissue engineering, focusing on the latest research progress in skin appendages (hair follicles and sweat glands) and vascularization, and summarizes current challenges and future development of 3D skin printing.